2021
DOI: 10.1177/2309499021996411
|View full text |Cite
|
Sign up to set email alerts
|

Identifying children at high risk for recurrence child abuse

Abstract: Purpose: To evaluate the characteristics of abused children, families and abusive event and to identify risk factors associated with recurrence of child abuse. Methods: Retrospective data from 133 children aged between 2 months to 15 years old who were diagnosed as abuse between year 2002 and 2017. Thirteen items related to characteristics of the child, families, abusive event were selected. These factors were analyzed by multivariate logistic regression model for association with repeated child abuse. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In Thailand between the years 2002 and 2017, 133 cases of child maltreatment were identified in a children's hospital and 45.10% of these cases were supported by parents. It was also shown that the presence of abusive relatives and age between one-and 10-years old lead to a higher risk of recidivism [28]. No abuse with recidivism was identified in our study, except for one case of family maltreatment already known to the competent authorities.…”
Section: Discussionsupporting
confidence: 54%
“…In Thailand between the years 2002 and 2017, 133 cases of child maltreatment were identified in a children's hospital and 45.10% of these cases were supported by parents. It was also shown that the presence of abusive relatives and age between one-and 10-years old lead to a higher risk of recidivism [28]. No abuse with recidivism was identified in our study, except for one case of family maltreatment already known to the competent authorities.…”
Section: Discussionsupporting
confidence: 54%
“…Some were harassed by parents and others refused contact with parents who continued to be threatening. A study by Wongcharoenwatana et al (2021) indicates that the risk of reoccurring CA is higher if the perpetrator is a parent. This was the case for some participants, although others had been violated by other family members.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood maltreatment is global social misbehavior, that in turn has caused psychological consequences and contributed to lower mental health status, drugs, or alcohol misuse along with physical morbidity and mortalityii. 32 Participants in this study have reported that 45.4% of them had emotional abuse, 36.7% of them had physical abuse, 65% were emotionally neglected and 25.3% were physically neglected. Risk factors that were associated with childhood maltreatment in this study sample were the mother's job, the caregiver or guardian, and the living standards of the family.…”
Section: Discussionmentioning
confidence: 70%